THE INFLUENCE OF THE PROBLEM-BASED LEARNING¬ MODEL ON THE RESULTS OF LEARNING MATHEMATICS IN CLASS V AT SDN RAWA GEMPOL - Winda Yuniar; Candra Puspita Rini; Yenni . (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This study aims to determine whether there are differences in the effect of the problem-based learning learning model on the learning outcomes of fifth grade mathematics at SDN Rawa Gempol. This study used a Quasi-Experimental method with a Nonequivalent Control Group Design research design. The population subjects in this study were all fifth grade students at SDN Rawa Gempol, totaling 51 students, by taking two classes as a sample, namely the VA class, which consisted of 25 students as the experimental class and the VB class, which consisted of 26 students as the control class. The data collection technique uses a test item instrument consisting of 10 valid and reliable questions. To test the pretest hypothesis in this study used the t test, from the results of the t test obtained tcount = 1.48 and ttable = 2.00, it can be concluded that there is no significant difference in effect between the average pretest value of the experimental class and the control class. Whereas for testing the posttest hypothesis from the t test obtained tcount = 2.51 and ttable = 2.00, it can be concluded that there is a significant difference in effect between the average posttest scores of the experimental class and the control class. This can be interpreted that the learning outcomes of fifth grade students using problem based learning learning models are higher than using conventional learning models.